Multichannel versus omnichannel: a price-segmented comparison from the fashion industry - Silva, Susana C. (2020)
Purpose – The purpose of this study is to explore and compare how fashion and apparel brands are using the multiple available channels to increase the number of touchpoints with clients by evaluating the use of multichannel and omnichannel strategies. Design/methodology/approach – To determine the differences between fashion and apparel brands in terms of marketing channel used, a multiple case study approach was selected based on a sample of nine wellknown and successful fashion brands from three different price segments. The research was carried out by analysing the online and mobile presence of the brands, company reports, news, magazines, and other types of articles. Findings – The results illustrate that fashion brands tend to act in the same way and have only slight differences concerning the number of channels and features available to clients despite the price segment they belong. The findings indicate that the brands under study have good channel integration, order tracking, online communication, and social media. Overall, the findings allow concluding that irrespective of the price segment, all fashion brands act almost in the same way and present only slight differences between the number of channels used and features available. Originality/value – The current study provides an innovative price-segmented comparison on channel use and integration by fashion brands’ and additional valuable information about channel strategy that can be used to guide new comparative research and helps new brands defining points-of-parity and points-ofdifference with regard to market standards.